2016
DOI: 10.1371/journal.pone.0148991
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Electronic Differential Diagnoses (DDX) Generators: A Systematic Review and Meta-Analysis

Abstract: BackgroundDiagnostic errors are costly and they can contribute to adverse patient outcomes, including avoidable deaths. Differential diagnosis (DDX) generators are electronic tools that may facilitate the diagnostic process.Methods and FindingsWe conducted a systematic review and meta-analysis to investigate the efficacy and utility of DDX generators. We undertook a comprehensive search of the literature including 16 databases from inception to May 2015 and specialist patient safety databases. We also searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
119
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 48 publications
0
119
1
1
Order By: Relevance
“…Interventions that could potentially improve clinical reasoning include advice to practice reflectively, [70][71][72] use of tools such as mnemonics and checklists, 73 and web-based decision support products that assist with differential diagnosis. [74][75][76] 'Debiasing' has been proposed as an approach to eliminate subconscious biases that contribute to error. 77 78 While many find the idea of focusing on cognitive biases and heuristics to improve clinical reasoning appealing, physicians find it difficult to characterise specific biases with any reliability and identify twice as many biases when outcome implies incorrect versus correct diagnosis.…”
Section: Improving Diagnostic Reasoningmentioning
confidence: 99%
“…Interventions that could potentially improve clinical reasoning include advice to practice reflectively, [70][71][72] use of tools such as mnemonics and checklists, 73 and web-based decision support products that assist with differential diagnosis. [74][75][76] 'Debiasing' has been proposed as an approach to eliminate subconscious biases that contribute to error. 77 78 While many find the idea of focusing on cognitive biases and heuristics to improve clinical reasoning appealing, physicians find it difficult to characterise specific biases with any reliability and identify twice as many biases when outcome implies incorrect versus correct diagnosis.…”
Section: Improving Diagnostic Reasoningmentioning
confidence: 99%
“…Such lists need careful construction, nonhierarchical team effort and adherence. Checklists have succeeded in reducing infections in intensive care units and operating rooms, but they fail if there is a lack of adherence . Continued reliance on human cognition: Even with its bias and inherent failures, human cognition is usually better than computer‐generated differential diagnostic algorithms and symptom checkers for office‐based clinician–patient encounters . Artificial intelligence is not, as yet, a solution for all errors or biases. Blinding: Visually based interpretive tasks, such as that of a pathologist examining specimens or a radiologist detecting imaging patterns, may benefit from a minimum of essential information from treating clinicians.…”
Section: Path Forward In Clinical Decision‐makingmentioning
confidence: 99%
“…Outcomes from the use of checklists have been mixed: Some research in real-world settings has demonstrated their utility and has provided a useful window on the expert's decision-making process (44,52,53,56,57). Other studies have found checklists to be of limited effectiveness in reducing errors in clinical decisionmaking or procedures (4,(58)(59)(60). Researchers have hypothesized that this lack of efficacy is due to underlying limitations within the checklist approach (61).…”
Section: The Checklist As a Tool To Reduce Errorsmentioning
confidence: 99%
See 2 more Smart Citations